In memory of the famous historian Talas Omarbekov (1948-2021) (Journal of history, 2023)
A year has passed since Talas Omarbekov, one of the leading figures of independent Kazakhstan in the field of creating national history, died on December 6, 2021. A historian and public intellectual, Omarbekov played a crucial role in the state's efforts to rehabilitate victims of the Stalin era and declassify Soviet archival documents. In addition, he headed two major research centers, "Alash" and "Republican Center for the Study of Traditional Civilizations of Central Asia", which produced the most important works on the history of Kazakhstan. But he was especially famous, probably, for opening the veil over the Kazakh famine of the 1930s, a terrifying catastrophe that led to the death of about a quarter of the population of Kazakhstan. In a series of works based on thorough archival research, Omarbekov introduced Kazakh-speaking readers to the horrors of hunger, and gained fame as the main expert on the issue in the country.